A novel CoN4-driven self-assembled molecular engineering for oxygen reduction reaction. (29th July 2021) - Kumar, Anuj; Das, Dipak Kumar; Vashistha, Vinod Kumar; Ibraheem, Shumaila; Yasin, Ghulam; Gautam, Sonali; Sharma, Vivek
Abstract: The poor kinetics of oxygen reduction reaction (ORR) invites a quest for the development of low-cost and efficient non-Pt electrocatalysts for fuel cells. Herein, a nanocomposite (g-[Co2 N8 ]) was synthesized by coordination assembly of CoN4 macrocyclic moieties on graphene surface. The CoN4 macrocyclic complex was characterized by UV–Vis, FT-IR, Mass, 1 H NMR and 13 C NMR spectral studies, whereas UV–Vis, FT-IR, and Mass spectral, Raman, XRD and TEM studies were utilized to characterize the nanocomposite g-[Co2 N8 ]. The results suggested that [CoN4 ] units are present in self-assembled [Co2 N8 ] species. Further, the nanocomposite g-[Co2 N8 ] was examined for ORR activity by employing cyclic and linear sweep voltammetry and found that the formal potential ( E 1/2 ) of g-[Co2 N8 ] (+0.90 V) was more positive than 20% Pt/C (+0.86 V), indicating a remarkable ORR performance of g-[Co2 N8 ] in comparison to 20% Pt/C, followed by 4e-mechanism. Moreover, the nanocomposite (g-[Co2 N8 ]) displayed better ORR activity in comparison to [CoN4 ] complex which can be attributed to the synergistic incorporation of endo and exo N4 –Co 2+ moieties in the [Co2 N8 ] species. In addition, g-[Co2 N8 ] electrocatalyst exhibited a comparable stability to 20% Pt/C catalyst after 5000 cycles. This work will help to design multi-metallic coordination polymers with similar or different metal ions in N4 -arrangement for various energy related electrocatalysis. Graphical abstract: Image 1 Highlights: CoN4 -complex was synthesized and characterized. Self-assembly of CoN4 -complex was carried out using coordination strategy. Self-assembled molecular catalyst immobilized on graphene synthesized and fully characterized. Self-assembled molecular catalyst immobilized on graphene exhibited excellent ORR activity.